Fear and loathing in the fog: the perceived (and persistent) vagaries of tenure standards among mass communication professors - Gould, Thomas H. P. (My University, 2013)
Perhaps nothing strikes more fear into the hearts of all tenure-track professors than the process itself. Are four papers in this journal good enough? Are eight papers in another okay? What if someone doesn’t like me or my area of research? These issues have plagued academia since the first essay was penned by the first researcher hundreds of years ago. While personal bias and journal preference continue to infect honest tenure reviews, solutions exist. This does not mean we have a magic bullet to solve issues of bullying or elitism. However, if we are honest in our desire to improve the Academy, we should avail ourselves of every possible tool for improvement. This essay is based on a survey sent to 2,500 mass communication educators. Of the almost 500 respondents, roughly 10% took the time to express emotions that ranged from fear and confusion to outright rage and anger, all because what ought to be clear is not. The author offers 10 ideas of how academia can improve its evaluation of new faculty, as well as a few suggestions regarding the unnecessary inclusion of personal issues in a process that ought to be about creating better researchers and teachers.
Keywords: Tenure standards; Professors